2019
DOI: 10.21873/anticanres.13620
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia as a Potential Predictor of Ipsilateral Breast Tumor Recurrence in Early Breast Cancer

Abstract: Background/Aim: The aim of this study was to investigate the association between lymphopenia after breast conserving therapy (BCT) and ipsilateral breast tumor recurrence (IBTR) in early breast cancer (EBC). Patients and Methods: We examined 216 EBC patients treated with partial mastectomy followed by radiotherapy (RT), none of whom received chemotherapy. Absolute lymphocyte counts (ALCs) during the two years after RT were collected from each patient: pretreatment ALC, ALC at 3-5 months (ALC1), ALC at 9-11 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…This is likely the first and the largest study examining risk factors for RIL in breast cancer patients, including radiation technique and dosimetric factors for lymphopenia and clinical significance. Our findings are consistent with the previous reports of several smaller studies (15,16). An early observational study of 34 patients by Stjernswärd et al in 1972 (18) reported long-term changes in PLC induced by RT in patients with breast cancer and their relation to tumor responses.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This is likely the first and the largest study examining risk factors for RIL in breast cancer patients, including radiation technique and dosimetric factors for lymphopenia and clinical significance. Our findings are consistent with the previous reports of several smaller studies (15,16). An early observational study of 34 patients by Stjernswärd et al in 1972 (18) reported long-term changes in PLC induced by RT in patients with breast cancer and their relation to tumor responses.…”
Section: Discussionsupporting
confidence: 94%
“…Our study of 735 patients demonstrated frequent RIL and heterogeneous reduction in lymphocytes after adjuvant radiotherapy. These findings have important clinical implications as a reduction in PLC is associated with immunosuppression, which significantly affects local control and survival in patients with breast cancer, as reported in several studies (6)(7)(8)15,16).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…And in these research, time points of LRBP were artificial selection, and most of them were before or after radiotherapy. 11,12 It seemed that obtaining LRBP of all time points, once a week, during radiotherapy and then finding the most representative one to investigate and analyze was a better choice. As radiotherapy leads to lymphopenia, the lowest lymphocyte count during radiotherapy might better represent immune suppression state caused by radiotherapy than lymphocytes during other time points, so LRBP at the time point of lowest ALC during radiotherapy was chosen in our study, which was different from the previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Among 221 patients, 49 (22.2%) patients reached DFS. The number of cases and the percentage of the metastatic and relapse sites were respectively: liver(11,22.4%), lymph gland(11,22.4%), chest wall (9, 18.4%), lung (9, 18.4%), bone (8, 16.3%), hydrothorax (3, 6.1%), and brain (2, 4.1%).…”
mentioning
confidence: 99%